Theatre of Testimony: An investigation in devising Asylum - Maedza, Pedzisai (Department of Drama, 2014)
The use of testimonies in performance is enjoying increased artistic and critical popularity on contemporary world stages and has a long and rich tradition on South African stages. Both internationally and locally, emerging and established playwrights working on migration and refugee issues are seeking to incorporate the testimony of asylum seekers into their work. This necessitates a need to critically reflect on the influences that shape and structure the staging of testimonies. This study argues that increased migration and the mounting number arrivals of asylum seekers on South African shores, has motivated at times violent interaction between host communities and the new arrivals. These incidents have inspired a distinct trend of testimonial performances around the concept of asylum. This dissertation uses Narrative analysis to read examples of contemporary theatre of testimony plays that examine this phenomenon. The study examines how playwright positioning informs the structuring of asylum testimonies on stage in addition to contextualising the ethical and moral complexities the playwright's positionality places on their practice. Through three case studies, the study interrogates how playwright positioning informs notions of authorship, authenticity, truth, theatricality and ethics. The study further investigates the challenges speaking for 'self' and speaking for the 'other' place on testimonial playwrights.